PLATELET INDICES AMONG SUBJECTS WITH AND WITHOUT DIABETES MELLITUS AND HYPERTENSION: A CROSS- SECTIONAL ANALYSIS AT KARACHI, PAKISTAN - Khan, Sikandar Hayat; Ahmad, Syed Azhar (Journal of Postgraduate Medical Institute, 2015)
Objective: To measure differences of platelet indices in subjects with and without diabetes mellitus and hypertension Methodology: This was a cross-sectional analysis from Jan-11 to Feb-2012. From a target population of non-pregnant adult subjects being advised a fasting blood glucose or OGTT for confirming or excluding diabetes, we finally selected 820 individuals for inclusion into study. Fifty known diabetics were also included in the study. Subjects were formally interviewed and sampled for fasting blood glucose, and platelet indices (including platelet count, plate -crit (PCT), mean platelet volume (MPV) and platelet distribution (PDW). The results of platelet indices were compared between 4 groups based on OGTT. Platelet indices were also compared between groups based upon post-load glycemic status and hypertension. Results: Age and MPV showed slight positive and significant correlations with fasting blood. [Age: r2=0.117 (p<0.001) and MPV: r2=0.116 (P=0.001); other platelet indices did not show significant correlations. Out of the 4 platelet in-dices studied, MPV and PCT were found to significantly increase from normo-glycemia to individuals with established diabetes mellitus in one way ANOVA analysis. Subjects demonstrating post load hyperglycemia (n=47) had high-er mean platelet volumes than individuals having post load normoglycemia (n=30) [MPV: 9.63 + 1.51vs 8.90 + 0.98, p=0.012]. Hypertensive subjects did not demonstrate higher MPV results than normotensive subjects in our study. Conclusion: Mean platelet volume and platecrit increases across various grades of hyperglycemia. However, the changes become quite prominent in subjects having established diabetes with marked hyperglycemia. Post load hyperglycemia was more predictive of rises in mean platelet volumes.